Student’s Scientific Argumentation Skills on Heat and Temperature - Rian Priyadi; Markus Diantoro; Parno Parno (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The weak of students' scientific argumentation skills in lessons has been a concern, especially in applying concepts of heat and temperature. Although heat and temperature are related to daily activity, it doesn’t ensure that students have the correct concept. This study purposes to describe students' scientific argumentation skills on heat and temperature. This research was conducted on 11th-grade in mathematics and science students in Senior High School 4 of Malang. This study found that students' scientific argumentation skills on average were at level 2nd and level 3rd. In addition, we found three patterns of scientific argumentation skills: (1) correct claims and evidence are accompanied by support for the evidence provided, (2) correct claims but use incomplete evidence, and (3) correct claims but the evidence is given wrong. This result it is expected to be the attention of teachers to implement learning models that can improve students' scientific argumentation skills.